Akupressure untuk Mengatasi Ketidaknyamanan Nyeri Punggung Ibu Hamil Trimester III di Desa Duren Kecamatan Tengaran - Fitriya, Wahida; Amelia Hesti Pradita; Isfaizah (Universitas Ngudi Waluyo, 2023)
As many as 70% of third trimester pregnant women experience back pain which makes pregnant women feel uncomfortable during pregnancy. Pain is a problem that is often encountered during pregnancy, especially when entering the third trimester. Pain causes a person to experience fear and anxiety, thereby increasing stress and experiencing drastic physiological changes during pregnancy. Discomfort felt by pregnant women needs to be overcome independently by using acupressure. Acupressure is a form of physiotherapy by providing massage and stimulation to certain points of the body which are useful for reducing aches, pains, tension and fatigue with the intention of re-activating the circulation of vital energy. Acupressure is safe for all populations, from children to the elderly, because acupressure has no side effects. Acupressure has a calming effect as well as regulating and stabilizing emotions. The method of community service in Duren Village, Tengaran District, is providing counseling and demonstrating about acupressure. Participants who took part in this activity were 14 pregnant women in Duren Village which was held on May 28 2023 at the Duren Village Hall. The results obtained are that pregnant women know complementary ways to reduce back pain in the third trimester so that pregnant women are able to apply acupressure to reduce back pain Abstrak Sebanyak 70% ibu hamil Trimester III mengalami nyeri punggung yang membuat ibu hamil merasa kurang nyaman selama kehamilan. Nyeri menjadi suatu masalah yang sering ditemui selama kehamilan terutama saat memasuki Trimester III. Nyeri menyebabkan seseorang mengalami ketakutan serta kecemasan sehingga meningkatkan stress dan mengalami perubahan fisiologi secara drastis selama kehamilannya. Ketidaknyamanan yang dirasakan ibu hamil perlu diatasi secara mandiri yaitu dengan menggunakan akupressure. Akupressure merupakan salah satu bentuk fisioterapi dengan memberikan pemijatan dan stimulasi pada titik-titik tertentu tubuh yang berguna untuk mengurangi sakit, nyeri, ketegangan dan kelelahan dengan maksud mengaktifkan kembali peredaran energi vital. Akupressure aman pada semua populasi mulai dari ana-anak hingga lansia karena akupressure tidak memiliki efek samping. Akupressure memiliki efek memenangkan serta mengatur dan menstabilkan emosi. Metode pengabdian masyarakat di desa Duren Kecamatan Tengaran yaitu memberikan penyuluhan serta mendemonstrasikan tentang Akupressure. Peserta yang mengikuti kegiatan ini berjumlah 14 ibu hamil di Desa Duren yang dilaksanakakan tanggal 28 Mei 2023 di Balai Desa Duren. Hasil yang diperoleh adalah ibu hamil mengetahui cara komplementer untuk mengurangi nyeri punggung trimester III sehingga ibu hamil mampu menerapkan Akupressure untuk mengurangi nyeri punggung.